Remote teaching methods in the organization of independent work of cadets - Hanifa Sarievna Galieva; Anna Victorovna Popova; Svetlana Victorovna Manetskaya (Вестник Майкопского государственного технологического университета)
The relevance of the article. The article examines modern forms and methods of conducting independent work in the distance mode when preparing future competitive specialists in maritime transport. The article notes the changes in the modern system of higher education associated with the reduction of practical, laboratory studies and an increase of independent work hours. It indicates the need for innovative computer-based learning technologies, that create conditions for effective assimilation of knowledge and formation of professional skills. The object of the research is the process of vocational training, namely, distance learning and phases of mastering educational material. Learning activities in the distance learning system are an opportunity to learn theoretical knowledge and to master practical learning skills outside the classroom. The subject of the research in this article is the process of organizing independent work of students as a means of forming professional competencies. The necessity of the optimal organization of independent work is analyzed taking into account the requirements of modern educational standards and forms of control. The research methods: theoretical methods (analysis of educational and methodical literature on the studied problem); empirical methods (various types of computer testing as one of the most common forms of control in the work of cadets and the role of a tutor in training activities used in verifying the performance of independent work). As a result, the effectiveness of the use of various types of testing in the independent work of students has been revealed. Innovative distance learning technologies and their combination with traditional methods are offered, which ensures the quality of self-organization and self-training of cadets.